Postoperative phlegmasia caerulea dolens: a case report and consideration of potential iatrogenic factors - Cahill, Ronan A (BioMed Central, 2007)
While the haemorrhagic consequences of anti-coagulants are well and frequently described in the surgical literature, the paradoxical prothrombotic tendencies of these drugs tend to be under-recognised due, perhaps, to their clinical infrequency. However, when these effects pertain, their consequences can be devastating. Here, we present a postoperative oncology patient who suffered a massive recrudescence of his lower limb venous thrombosis immediately after discontinuation of his heparin infusion, despite seemingly being adequately anticoagulated by warfarin therapy (INR > 2.0). We intend this case to graphically illustrate the theoretical considerations that must govern the perioperative use of these drugs in high-risk patients.